Profile of Student Learning Outcomes on Learning Differentiated on Virus Concepts - Utami, Anggi Anrisyah; Prastiningsih, Danik; Toyyibah, Toyyibah (Universitas Sultan Ageng Tirtayasa, 2023)
Each student has various characteristics in carrying out the learning process. But so far, learning is often done without regard to this diversity. The research method in this research is the descriptive research method. The instruments used were initial assessment instruments to identify learning styles, low vision PDBK special needs assessments, and daily assessment instruments for Virus learning concepts. Identifying students' learning styles determines the type of learning media given to students. Students with audio learning and visual learning styles are given learning media in audio-visual videos, while students with kinesthetic learning styles are given learning media in the form of puzzles. From the results of observations, it was found that one student with special needs (PDBK) had low vision and was then given learning media in the form of a text/PowerPoint file with a larger and thicker image size. Differentiated learning based on learning styles and the needs of students can improve student learning outcomes, including low vision PDBK. This can be seen from the results of the daily assessment of viral concept, which has increased. The research results show that differentiated learning by providing different learning media according to the learning styles and special needs of students can improve student learning outcomes on Virus concepts.